Clinical and demographic analysis of patients with colorectal cancer screened at a reference hospital in Southern Brazil: comparative study based on age (Retrospective cohort study) - Otavio de Carvalho Modaffar Al-Alam; Rafael Jose Vargas Alves; Adele Lanziani Fae; Camile Neves Cardoso; Jamille Rizzardi Lava; Joanna Palmeira Castro; Julia Signori; Larissa Grazziotin Claudino; Tales Barros Cassal Wandscheer; Victor Viecceli Villarinho; Affoue Prisca Michelle S. Yao; Claudia Giuliano Bica (BMC Gastroenterology)
Abstract Background Colorectal cancer (CRC) is a prevalent and lethal malignancy. This study examines differences in clinical and prognostic characteristics of CRC between patients under 50 years and those aged 50 and above, treated at a reference hospital in Southern Brazil. Methods A retrospective cohort study was conducted, analyzing data from the Cancer Hospital Registry in Porto Alegre, RS. Patients diagnosed with colon or rectal adenocarcinoma between January 2013 and December 2017 were included. Variables analyzed included family history, alcoholism, smoking status, clinical staging, tumor laterality, clinical presentation, CEA levels at diagnosis, adjuvant chemotherapy, and neutrophil-to-lymphocyte ratio. Results The study cohort included 1,121 patients, with 85% aged 50 years or older, and 15% younger than 50 years. Significant differences were observed in smoking status and clinical presentation, with younger patients presenting with a higher prevalence of obstruction/subocclusion at diagnosis, which may reflect differences in clinical presentation due to delayed diagnosis. Conclusions Age and lifestyle factors, particularly smoking, significantly influenced the clinical presentation and management of colorectal cancer. These findings underscore the importance of targeted prevention strategies and personalized treatment approaches for younger CRC patients.